Safety profile of sacituzumab govitecan in patients with breast cancer: A systematic review and meta-analysis - Maria Inez Dacoregio; Isabella Michelon; Caio Ernesto do Rego Castro; Francisco Cezar Aquino de Moraes; Guilherme Rossato de Almeida; Lis Victória Ravani; Maysa Vilbert; Ricardo Lima Barros Costa (Breast)
Background: Sacituzumab Govitecan (SG), a first-in-class anti-trophoblast cell surface antigen-2-directed antibody-drug conjugate (ADC), has shown clinically meaningful improvement in outcomes of patients with breast cancer (BC). However, it has also been accompanied by significant toxicity. Thus, we conducted a systematic review and meta-analysis to evaluate the safety and tolerability of SG in this patient population. Methods: We comprehensively searched PubMed, Embase, and Cochrane databases, and ASCO and ESMO websites for clinical trials (CTs) assessing the safety of SG in BC patients. All analyses were performed in R software (v.4.2.2) using random effects models. Heterogeneity was assessed using I2 test. Results: Seven studies – three randomized clinical trials (RCTs) and four single-arm phase I/II – were included, comprising 928 patients receiving SG and 576 on treatment of physician's choice (TPC). Most patients had triple negative BC (54.4 %, n = 505), metastatic disease (89.8 %, n = 833), and were heavily pretreated (at least two lines of prior therapy). Most common all-grade adverse events (AEs) were: neutropenia (70 %, 95 % CI, 64–76 %), followed by nausea (62 %, 95 % CI, 55–68 %), diarrhea (54 %, 95 % CI 47–60 %) and anemia (51 %, 95 % CI, 38–65 %). Regarding high-grade AEs, 46 % of patients developed grade ≥3 neutropenia. Compared to TPC, we observed a higher risk of neutropenia (OR 3.11, 95 % CI 1.62–5.99, I2 = 81 %; p < 0.001), diarrhea (OR 6.82, 95 % CI 3.99–11.66, I2 = 64 %; p < 0.001) and anemia (OR 2.26, 95 % CI 1.20–4.27, I2 = 78 %; p = 0.012) for those on SG. Dose reductions and treatment discontinuation were reported in 22 % and 4 % of patients, respectively, and 19 deaths (2 %) were documented. Most of them were not deemed to be treated-related. Conclusion: This systematic review and meta-analysis provides extensive data on the safety and management of SG toxicity in BC patients across clinical trials. Concerning rates of neutropenia, nausea diarrhea, and anemia were reported. We highlight the need for protocols establishing prophylactic measures and strategies to mitigate SG-related toxicity.